Exploring teachers’ teaching skills: conceptual definition, documentation, and categorization - Filippos Evangelou; Konstantina Giannopoulou (Institute of Advanced Engineering and Science, 2026)
This study investigates the conceptual definition and categorization of teaching skills, aiming at their systematic identification and analysis within the context of the educational process. Through a systematic literature review conducted in accordance with the preferred reporting items for systematic review and meta-analysis (PRISMA) statement guidelines, a broad spectrum of 27 teaching skills is documented, each linked to key aspects of teaching practice, such as lesson planning, classroom management, and assessment. The diversity of theoretical approaches to the taxonomy of skills highlights the need for a coherent and functional categorization, which-based on their common characteristics-consists of eight general domains of skills, such as teaching design skills and teaching implementation skills. This categorization enables the implementation of more targeted and effective interventions for both the education of pre-service teachers and the professional development of in-service teachers. The present study, as an element of originality, offers one of the first systematic categorizations of teaching skills into eight coherent domains. The practical implications of the study lie in providing a structured framework for teacher self-assessment and the design of professional development programs based on targeted teaching skills. The findings underscore the need for further research into the nature, development, and practical implementation of teaching skills in classroom settings.